Paraneoplastic pemphigus associated with Castleman disease: A multicenter case series. Issue 1 (20th September 2022) - Barry, Kelly K.; Plumptre, Isabella; Bazewicz, Christopher G.; Green, Brian P.; Treat, James R.; Hughes, Meagan; Morel, Kimberly D.; Wiss, Karen; Liang, Marilyn G.
Abstract: Introduction: Paraneoplastic pemphigus (PNP) is a rare, often fatal, autoimmune blistering disease of the skin and mucous membranes. In children, PNP is frequently associated with Castleman disease (CD). This series describes five cases of PNP associated with CD. Methods: Data were collected retrospectively from the medical records of patients with a diagnosis of PNP and CD from January 2013 to June 2022. Patients ≤22 years old with clinical and immunopathologic evidence of PNP were included; CD was diagnosed histopathologically. Results: Two children, two adolescents, and one young adult (two males, three females) were included. The average age at disease presentation was 11.8 years (range: 7–22 years). Oral ( n  = 5) and anogenital ( n  = 3) mucositis were common. Four patients had "unicentric" CD (UCD); one patient had "multicentric" CD (MCD). Castleman tumors were in the retroperitoneum ( n  = 4) or axilla ( n  = 1). One patient had myasthenia gravis without thymoma. Three patients had bronchiolitis obliterans (BO). Three patients had complete resection of their CD; two had partial resection. Three patients remain alive with a median follow‐up of 13 months (range: 12 months to 13 years); two are clinically stable with resolution of mucocutaneous lesions; one has persistent BO requiring ongoing ventilatory support. Patients who remain alive had UCD with complete resection; all deceased patients had partial resection and BO. Conclusion: Most patients had UCD, and the retroperitoneum was the most common location. Patients with MCD, incomplete resection, and BO died; patients with UCD and complete resection remain alive, even in the setting of BO. Consideration of PNP is critical when pediatric patients present with mucositis as PNP may be clinically indistinguishable from more common causes of mucositis.